1980
DOI: 10.1128/jb.144.1.274-278.1980
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and transport properties of the glycerol facilitator of Escherichia coli

Abstract: The specificity of the glycerol facilitator (glpF) of Escherichia coli was studied with an osmotic method. This transport system allowed the entry of polyols (glycerol and erythritol), pentitols, and hexitols. The analogous sugars were not transported. However, urea, glycine, and DL-glyceraldehyde could use this pathway to enter the cell. The glpF protein allowed the rapid efflux of preequilibrated xylitol. Glycerol surprisingly did not inhibit the uptake of xylitol, and xylitol only slightly reduced the uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(134 citation statements)
references
References 14 publications
6
125
0
3
Order By: Relevance
“…GlpF has been shown to facilitate the diffusion of small polyols into E. coli cells (Heller et al, 1980). The possibility that the prokaryotic GlpF protein is synthesized in oocytes but is not functionally expressed in the oocyte plasma membrane was investigated by performing a glycerol uptake assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GlpF has been shown to facilitate the diffusion of small polyols into E. coli cells (Heller et al, 1980). The possibility that the prokaryotic GlpF protein is synthesized in oocytes but is not functionally expressed in the oocyte plasma membrane was investigated by performing a glycerol uptake assay.…”
Section: Resultsmentioning
confidence: 99%
“…All protein members of the MIP family have six putative membrane spanning domains, exhibit a channel-like structure, and a few have been shown to mediate transmembrane transport. The bacterial protein GlpF facilitates the transport of glycerol and other small straight chain polyols across the cytoplasmic membrane (Heller et al, 1980;Sweet et al, 1990). The human protein CHIP28 has recently been shown to form water channels (Preston et al, 1992;van Hoek and Verkman, 1992;Zeidel et al, 1992), and the bovine MIP protein itself forms ion channels when incorporated into lipid bilayers (Zampighi et al, 1985;Ehring et al, 1990).…”
Section: Oxford University Pressmentioning
confidence: 99%
“…These findings indicate that 1zqpZ is monocistronic, a feature consistent with the general nature of the aquaporins which are known to be constitutively activated without any accessory proteins. The monocistronic nature further distinguishes uqpZ from its E coli sequence-homolog, gIpf (Heller et al, 1980;Sweet et al, 1990), which encodes a glycerol transporter and is contained within an operon comprising several genes involved in glycerol metabolism, thus supporting the hypothesis of a large phylogenetic separation…”
Section: Discussionmentioning
confidence: 93%
“…Genes whose deduced proteins have sequences and topological similarities to AqpZ are present in the genomes of the Gram-negative bacterium Huemuphilus influenzue (Fleischmann et ~2, 1995) and in a prokaryote lacking a cell wall and having a minimal set of functional genes such as Mycoplasmu genitulium (Fraser et UI, 1995). Bacteria also expresses g&F, an uqpZ-sequence homolog which is included within an operon (Heller et al, 1980;Sweet et al, 1990) and encodes a glycerol facilitator which is only weakly permeable to water (Maurel et ~2, 1994;Calamita et al, 1995). As revealed by phylogenetic analyses, functional distinctions between AqpZ and GlpF probably resulted from the ancient divergence in a primordial gene (Calamita et al, 1995;Park and Saier, 1996), however, uqpZ and glpF genes are not present in the genome of the archaeon Methunococcus junnaschii (Bult et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The Escherichia coli glycerol facilitator protein (GlpF) was discovered long before aquaporins were recognized (Heller et al, 1980), but the second homolog (AqpZ) was discovered more recently (Calamita et aL, 1995). E. coli genome sequencing has confirmed that these are the only two aquaporin homologs in that bacteria.…”
Section: B Microbial Homologsmentioning
confidence: 99%